PELAPORAN KEUANGAN ATAS PENGELOLAAN RETRIBUSI PASAR KABUPATEN REJANG LEBONG TINJAUAN EFISIENSI DAN EFEKTIVITAS - Feriyani, Dora; Fachruzzaman, Fachruzzaman; Martiah NP, Lisa (JURNAL FAIRNESS, 2013)
This study aims to determine the efficiency and effectiveness of market retribution and to know how the financial reporting procedures contained in the Revenue District Rejang Lebong. The data used is the realization data charges from Dispenda market from 2008 to 2012. The approach used for this study is the use calculation of the level of efficiency and effectiveness, and other supporting data, if it still raises the question of the researcher's approach using observation, interviews and in-depth interviews. The effectiveness and efficiency of market levies not stand alone, but relates and systemed with other factors, such as the quality factor of human resources, infrastructure, quality of bureaucracy that is not convoluted, the level of supervision and reporting is crucial to meet the target. Increased levels of these factors on the higher level of effectiveness and efficiency of market retribution will continue also in the level of development revenues conversely the lower the quality of these factors the lower the level of retribution income markets will continue also in lower revenue growth rate native to the area. In the calculation of the level of effectiveness for the past 5 years of research targets because doing surveillance on a regular basis by the Dispenda, infrastructure improvements every year, the human factor is responsible to his duty, and financial reporting charges paid market every day to Dispenda. Officers assigned to collect levies market is not so much the operational budget is not so big.